Greeting Tradition to Build Interreligious Peace in Indonesia: Multicultural Education Perspective - Leonardus Samosir; Kallaya Masserie Arane; Lydia Seruni Endrardewi; Mochamad Ziaul Haq (Universitas Muhammadiyah Malang, 2023)
The study aims to discuss greetings as an essential factor in creating interfaith peace. As a multicultural country, Indonesia needs peaceful efforts to help create a safe and harmonious situation. The article uses qualitative research methods by analyzing primary and secondary sources. Primary sources are based on books or journals resulting from serious research and from authors who are authoritative in the field of peace studies. In contrast, secondary sources are based on journal articles and textual studies of previous research results. This research analysis study used Johan Galtung's thesis regarding the importance of using creative ways to build relationships with a pluralistic religious community. Therefore, as a tradition in each religion, the greeting is not a new but a significant effort to re-make it as a way of bonding peace between religions. The research states that: First, multiculturalism describes the diversity of Indonesian culture and the social conditions of its people; Second, the interpretation and dissemination of greetings in the doctrine of religion means peace. This fact contributes to the creation of good practices in a pluralist-oriented society. Third, greetings become a vital part of the multicultural educational process in educational institutions. In this case, multicultural education as a perspective used to analyze the object of this research has proven to build students' knowledge based on appreciation and acceptance of groups with different beliefs. Therefore, this study confirms that religious greetings can internalize the values of peace in social and spiritual life in Indonesia, especially as part of the learning process in multicultural education.